2022
DOI: 10.1016/j.aucc.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Australian critical care nurses' knowledge, preparedness, and experiences of managing SARS-COV-2 and COVID-19 pandemic

Abstract: Background COVID-19 has again highlighted the crucial role of healthcare workers in case management, disease surveillance, policy development, and healthcare education and training. The ongoing pandemic demonstrates the importance of having an emergency response plan that accounts for the safety of frontline healthcare workers, including those working in critical care settings. Objectives To explore Australian critical care nurses’ knowledge, preparedness and experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
3
14
0
1
Order By: Relevance
“…Regarding the evidence found, the results of this review coincide with other reviews retrieved (53,54) regarding the barriers to the performance of their professional role; some of the relevant factors, which have been developed by several authors, are "fear" (3,14,46), uncertainty (55), psychological stress and the reluctance of healthcare professionals -especially nurses and nursing assistants (56)to work with patients infected with emerging infectious diseases in an environment of scarce personal protective equipment (46,48) and, therefore, the fear of bringing the infection to their homes and families (48,57,58). This situation has not been addressed by governmental and health agencies, nor by the ICN (International Council of Nurses); the aforementioned institution, although it has recently published the 12 main priorities for the COVID-19 pandemic (59), did not consider in any of the points of the declaration the protection of the fundamental pillar of every human being, and of course, of a healthcare professional, namely, their families.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Regarding the evidence found, the results of this review coincide with other reviews retrieved (53,54) regarding the barriers to the performance of their professional role; some of the relevant factors, which have been developed by several authors, are "fear" (3,14,46), uncertainty (55), psychological stress and the reluctance of healthcare professionals -especially nurses and nursing assistants (56)to work with patients infected with emerging infectious diseases in an environment of scarce personal protective equipment (46,48) and, therefore, the fear of bringing the infection to their homes and families (48,57,58). This situation has not been addressed by governmental and health agencies, nor by the ICN (International Council of Nurses); the aforementioned institution, although it has recently published the 12 main priorities for the COVID-19 pandemic (59), did not consider in any of the points of the declaration the protection of the fundamental pillar of every human being, and of course, of a healthcare professional, namely, their families.…”
Section: Discussionsupporting
confidence: 72%
“…The search strategy used achieved an initial retrieval of 11,031 potential articles for the study, out of which 32 articles were finally included in the final sample (Table 1 Once the 32 selected studies had been evaluated (Table 1), it was observed that more than half of the articles stemmed from the Americas: Canada (3,35), The USA (1, 23-30, 34, 37, 45), Brazil (47) and one article that refers to the American continent in general (3); the rest of the evidence is distributed across studies from Asia (10, 14,32,38,40,40,42,43,43,44,49), Europe (39,41,46), Oceania (6,31,48), and Africa (33); therefore, all the articles are written in English. Regarding the journals where these articles were published, it was noted that all were published in journals indexed in the Proquest, Scopus, and Pubmed databases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is a growing body of research on aspects of COVID-19 related health literacy of the general population [4,15,16,22] or specific populations, e.g., migrants, children, students, or patients [8][9][10][11]13,[19][20][21]23], little is known about the COVID-19 related health literacy of healthcare professionals, such as physicians, nurses, or psychologists. Since 2020, many studies have investigated the knowledge, attitude, and behavior of healthcare professionals worldwide [24][25][26][27][28][29][30][31][32][33][34]. The results indicate a lack of adequate knowledge about COVID-19 in many cases (6-42%) [24,25,27,32].…”
Section: Introductionmentioning
confidence: 99%